Penyusunan Paket Wisata Edukasi Dan Video Promosi Subak Intaran Desa Sanur Kauh Denpasar Bali - Purnami Rusadi, Ni Wayan; Pande Made Ari Ananta Paramarta; Ni Putu Tiya Paristha; Gusti Ayu Marnisa Dewi (Joong-Ki : Jurnal Pengabdian Masyarakat, 2023)
Subak Intaran is one of the agricultural subaks that is still active in Denpasar City, precisely in Sanur Kauh Village, South Denpasar. Which is divided into two parts, namely Subak Intaran Barat and Subak Intaran Timur which have a productive land area of around 98 hectares. This study aims to prepare educational tour packages and make promotional videos for Subak Intaran, Sanur Kauh Village, Denpasar, Bali. Where to apply qualitative methods by means of data collection, observation, in-depth interviews, and literature review. Data collection materials include image attachments, observation sampling to produce any potential there, which can be made into tour packages, interviews to produce this article. The results of the study showed that Subak Intaran is one of the subaks which currently has the potential not only for natural agricultural tourism, jogging tracks, but also tourism potential which can be developed and made into various tour packages including planting packages, harvest packages and shopping packages for self-harvest products.